Unified representation of a certain class of harmonic univalent functions defined by Dziok-Srivastava operator - M. K. Aouf (Le Matematiche, 2014)
In this paper, we investigate several properties of the harmonic class defined by the modified Dziok-Sirvastava operator, obtain distortion theorem, extreme points, convolution condition, convex combinations and integral operator for this class. Some of our results generalize previously known results.